Real-world pharmacovigilance analysis of galsulfase: a study based on the FDA adverse event reporting system (FAERS) database - Li, Shangze; Huang, Runcheng; Meng, Yuanyuan; Liu, Yijia; Qian, Jiao; Zou, Junjie; Yang, Jun (Frontiers in Pharmacology, 2024)
Background Associated with enzyme deficiencies causing glycosaminoglycans (GAGs) accumulation, mucopolysaccharidosis type VI (MPS VI) is lysosomal storage disorder. In the treatment of MPS VI, galsulfase (Naglazyme) is commonly used as an enzyme replacement therapy (ERT). There remains a need for comprehensive real-world data on its safety and associated adverse events (AEs). Objective An analysis of the FDA Adverse Event Reporting System (FAERS) database will be conducted to identify potential risks and adverse reactions associated with galsulfase in real-life settings. Methods The FAERS database was used to extract data from Q2 2005 to Q4 2023. A total of 20,281,876 reports were analyzed after duplicate elimination, with 3,195 AE reports related to galsulfase identified. The association between galsulfase and AEs was investigated by utilizing four algorithms: reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian confidence propagation neural network (BCPNN), and multi-item gamma Poisson shrinker (MGPS). The analysis focused on the timing of onset, signs of AEs, and clinical significance. Results Twenty seven organ systems were involved, and significant system organ classes (SOCs) included respiratory, thoracic and mediastinal disorders, and infections and infestations. At the PT level, 72 PTs corresponding to 15 SOCs were identified, with some AEs not previously mentioned in the product label. AEs associated with galsulfase had a median onset time of 1,471 days, with over half of the cases occurred within the first 5 years of treatment initiation. Conclusion This investigation delivers an exhaustive and indicative assessment of galsulfase’s safety profile, grounded in authentic, real-world evidence. The findings emphasis the importance of continuous safety surveillance and the emergence of new AEs. The identification of previously unreported urologic adverse events, such as glomerulonephritis membranous and nephritic syndrome, warrants further investigation. The study emphasizes the need for enhanced pharmacovigilance to ensure patient safety and the effectiveness of galsulfase treatment.